Recent advances in the techniques for demographic analysis - Saxena, P. C. (Prem Chandra), 1939-; Talwar, Prem P., 1936-; Indian Association for the Study of Population (Bombay : Himalaya Publishing, 1987)
Papers presented at a workshop held in Bombay, 1982, organized by the Indian Association for the Study of Population.
Includes bibliographies.
Keywords: Demography -- Congresses; Cohort analysis -- Congresses; India -- Population -- Congresses